20-Hydroxyeicosatetraenoic Acid as a Predictor of Neurological Deterioration in Acute Minor Ischemic Stroke. Issue 12 (December 2016) - Yi, Xingyang; Han, Zhao; Zhou, Qiang; Lin, Jing; Liu, Ping
Abstract : Background and Purpose—: The relationship between high plasma 20-hydroxyeicosatetraenoic acid (20-HETE) levels and neurological deterioration (ND) has not been investigated in patients with acute minor ischemic stroke. Method—: We conducted a prospective, multicenter observational study in patients with acute minor ischemic stroke. Plasma levels of 20-HETE were measured at admission in all patients. The primary end point of the study was ND within 10 days after admission. The degree of disability was assessed using modified Rankin scale at 3 months after admission. Results—: A total of 322 patients were enrolled, of which 85 patients (26.4%) developed ND. Mean 20-HETE level was 1687±158 pmol/L. On multivariate analyses, high level (>1675 pmol/L) of 20-HETE was an independent predictor of ND (third and fourth quartiles). Neurological deterioration was associated with a higher risk of poor outcome (modified Rankin scale scores 3–6) at 3 months. Conclusions—: ND is fairly common in acute minor ischemic stroke and is associated with poor prognosis. Elevated plasma level of 20-HETE may be a predictor for ND in acute minor ischemic stroke. Abstract : Supplemental Digital Content is available in the text.